2019
DOI: 10.4028/www.scientific.net/msf.955.50
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Clinker Containing Lithium

Abstract: Nowadays, in industrial production, lithium consumption is strongly increasing and it can be assumed that waste material with an increased content of this metal could also appear. One of the most important sectors where different types of waste can be utilized is the cement industry. Therefore, it is desirable to monitor the influence of lithium on formation and properties of the clinker. In the presented work, this effect was monitored in laboratory conditions up to 5 wt.% Li2O. X-ray diffraction, DTA and opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recently, it has been discovered that lithium additionally causes the alite to decompose into a microcrystalline mixture of belite and free lime, depending on its content in clinker and the clinker cooling rate. At the same time, cement prepared from clinker with 1 wt.% Li 2 O burned at 1350°C showed the same technological parameters as conventional OPC (Ordinary Portland cement) 10,11 …”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, it has been discovered that lithium additionally causes the alite to decompose into a microcrystalline mixture of belite and free lime, depending on its content in clinker and the clinker cooling rate. At the same time, cement prepared from clinker with 1 wt.% Li 2 O burned at 1350°C showed the same technological parameters as conventional OPC (Ordinary Portland cement) 10,11 …”
Section: Introductionmentioning
confidence: 71%
“…At the same time, cement prepared from clinker with 1 wt.% Li 2 O burned at 1350 • C showed the same technological parameters as conventional OPC (Ordinary Portland cement). 10,11 Kakali et al 12 found out that the addition of CuO affects the formation of silicates and aluminates. CuO mainly promotes the formation and growth of alite crystals at lower temperatures and alters the crystallisation processes upon cooling clinker.…”
Section: Introductionmentioning
confidence: 99%
“…Given the error that the Rietveld refinement has, this difference is negligible. Recent study [22] clarifies this effect of Li by significant reduction in the temperature of the clinker melt formation and a decrease in its viscosity. Lithium causes a partial to complete decomposition of the alite into microcrystalline mixture of belite and free CaO depending on Li 2 O content and cooling rate.…”
Section: Phase Analysismentioning
confidence: 94%
“…The main components are quicklime, a source of SiO2 and various activators. As activators, Li and Cu were chosen, based on previous works [10,11], followed by KOH and sodium phosphate.…”
Section: Introductionmentioning
confidence: 99%